High spatial resolution soil data for watershed modeling: 2. Assessing impacts on watershed hydrologic response - Sheshukov, Aleksey Y.; Daggupati, Prasad; Douglas-Mankin, Kyle R. (My University, 2011)
Spatial resolution of soil datasets used in watershed modeling is known to affect simulated hydrological response. Two databases, the Soil Survey Geographic (SSURGO) and the State Soil Geographic (STATSGO), provide publicly available soil datasets for hydrologic modeling of watersheds in the U.S. This study evaluated three soil representations using the Soil and Water Assessment Tool (SWAT) model to simulate hydrologic response in the Black Kettle Creek Watershed in Kansas, U.S.A.: SWAT using either 1) STATSGO data, or 2) SSURGO data, or 3) a third HYBRID model that used STATSGO soil data with the more refined SSURGO spatial distribution. The SSURGO-ArcSWAT utility was used to facilitate development of detailed soil data for SWAT modeling projects. The SWAT model with STATSGO data produced the greatest surface runoff and streamflows among the three models, especially during higher-rainfall events, in part due to overrepresentation of hydrologic group C and D soils. The SWAT model with SSURGO data produced the best calibration statistics, and exhibited the least flashy surface runoff behavior. The model with HYBRID soil data exhibited lower percentage bias and improved Nash-Sutcliffe model efficiency compared to the model with STATSGO soil data, and it was attributed to increased spatial resolution of hydrologic response units (HRUs) inherited from the SSURGO soil dataset. Calibration results and hydrologic impact may vary in other areas of the United States and in the world, but benefits of using SSURGO soil dataset are expected to come from both greater resolution of soil property data and a greater number of HRUs.
Keywords: Hydrologic Modeling; SSURGO; STATSGO; SWAT